Pengaruh Bahan Tambah Bakteri Bacillus Subtilis Terhadap Kuat Tekan Dan Kuat Lentur Beton Di Lingkungan Sulfat - Fitrana, Yaniarto; Djauhari, Zulfikar; Yuniarto, Enno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The application of concrete to the sulfate environment potentially cause damage to concrete. The use of bacteria in concrete can be a concrete innovation to recover concrete (Self Healing Concrete) from the problem of concrete cracks. This study was conducted to examine the effect of Bacillus Subtilis bacteria on compressive strength and flexural strength of concrete in the sulfate environment. This research was conducted by adding 25 ml Bacillus Subtilis bacteria with concentration of 105 CFU/ml into a concrete mixture. Test objects were plain concrete beams with a size of 60x15x15 cm and cylinders with a diameter of 15 cm and a height of 30 cm. The variation of test specimens consisted normal concrete soaked in normal water (BNN), bacterial concrete soaked in normal water (BBN) and bacterial concrete soaked in sulfate solution (BBS). Two tests were carried out, namely compressive strength test and flexural strength test. The test result showed that the compressive strength of BBS at the age of 28 and 56 days was 14% and 24% lower then that of BNN. Comparing to BBN, compressive strength of BBS at 28 and 56 days were lower 26% and 34%, respectively. Furthermore, the test result showed that the flexural strength of BBS at the age of 28 and 56 days was 14% and 9% higher than that of BN. Comparing to BBN, flexural strength of BBS at 28 and 56 days were higher 13% and 2%, respectively. The addition of bacteria to the concrete in the sulfate environment increases the flexural strength of the concrete.Keywords: Self Healing Concrete, sulfate environment, Bacillus Subtilis, compressive strength, flexural strength.Â